HUBUNGAN PRESEPSI SISWA DESAIN PEMODELAN DAN INFORMASI BANGUNAN KELAS XI SMKN 7 BALEENDAH TENTANG HYBRID LEARNING DENGAN MOTIVASI BELAJAR DALAM MATA PELAJARAN KONTRUKSI JALAN DAN JEMBATAN - Satrio Arif Abdulla, - (2022)
Hybrid learning is learning that combines learning delivery strategies using face-to-face (offline) activities, computer-based learning (online) internet and mobile learning. Through hybrid learning, all learning resources can "facilitate the learning process for the person learning", as the learning methods used are appropriate to overcome educational declines due to the pandemic and students' understanding of learning itself. The purpose in this study is to find out the relationship of perceptions of DPIB students of SMKN 7 Baleendah about the method) descriptive statistics is a tool used to describe or describe the data that has been collected as it is but not to make conclusions or generalizations. The relationship between the perception of class XI DPIB students of SMKN 7 Baleendah towards Hybrid Learning learning with student motivation in the subject of road and bridge construction. It has a positive level of relationship but is not significant in terms of student motivation. For schools and teachers, especially in the subject of Road and Bridge Construction, the hybrid learning model should be reviewed and continue to be developed by creating a good, conducive, and comfortable learning atmosphere, creating or using learning methods that are in accordance with student characteristics. With this new learning method, namely hybrid learning, it can increase student motivation in learning when the world is hit by a pandemic, this learning method is important to apply because it is more effective in the learning process because learning can be through offline and online simultaneously. Furthermore, researchers are expected to be able to develop this research with a wide scope of objects and variables developed by adding other indicators in the research instrument.